2023
DOI: 10.1186/s12903-023-03357-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of concentrated growth factor (CGF) in the surgical treatment of oral diseases: a systematic review and meta-analysis

Liang Chen,
Jing Cheng,
Yu Cai
et al.

Abstract: Background Concentrated growth factor (CGF), a new autologous platelet concentrate, has been widely investigated to the adjunctive treatment of oral diseases. This study aims to evaluate the efficacy of CGF in the surgical treatment of oral diseases. Methods MEDLINE, Web of Science, Scopus, Cochrane, and EMBASE databases were searched up to July 2023. Only randomized clinical trials were included. The methodologic quality was evaluated by the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The degree of postoperative swelling was not specifically assessed in this study, but a reduction in swelling would also significantly reduce the patient’s postoperative pain and discomfort. A meta-analysis on CGF [ 33 ] also suggested that CGF has the potential to significantly improve healing and reduce pain within one week of oral surgery. The mechanism behind pain relief lies in the fact that the fibrin structure of CGF acts as a scaffolding material and reservoir to transfer growth factors, including PDGF, TGFb1, VEGF, and proinflammatory cytokines, which can greatly reduce pain caused by inflammatory responses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of postoperative swelling was not specifically assessed in this study, but a reduction in swelling would also significantly reduce the patient’s postoperative pain and discomfort. A meta-analysis on CGF [ 33 ] also suggested that CGF has the potential to significantly improve healing and reduce pain within one week of oral surgery. The mechanism behind pain relief lies in the fact that the fibrin structure of CGF acts as a scaffolding material and reservoir to transfer growth factors, including PDGF, TGFb1, VEGF, and proinflammatory cytokines, which can greatly reduce pain caused by inflammatory responses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CGFs may be more suitable than PRP or bFGF for the treatment of olfactory dysfunction. CGF has been clinically applied and shown to be effective [ 45 ]. Zhao et al used CGF for mucosal defects of the nasal septum and reported efficacy and no side effects [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the special CGF speed‐changing centrifuge made by Hersey Company and the special vacuum negative pressure blood vessel according to the preparation procedure of manual, the venous blood suitable for the size of tooth extraction socket was collected and put into the rotating cylinder of the centrifuge; after centrifugation for 15 min, the blood in the tubes was taken out. It was obvious that the blood in the vessel had been divided into three layers, and the lighter‐coloured serum on the top layer and the precipitate of red blood cells on the bottom layer was discarded, the middle layer gel, which is called CGF gel, was cut into pieces of 2 mm in size and put into a normal saline solution for use 17 , 18 ; then carefully clean the blood clots in the sockets, rinse with normal saline and then fill the sockets with the crushed CGF gel, a Hemostatic Wound Healing Gauze patch was then applied to the wound surface to prevent CGF gel from falling off or food residue from contaminating the tooth extraction pit. All operations are performed by the same surgeon.…”
Section: Methodsmentioning
confidence: 99%